Caries experience in Indian children with cleft lip and palate – an observational study from a tertiary care centre - Mukhopadhyay, Santanu; Mukhopadhyay, Prasun (Publishing Office of the University of Rzeszow, 2024)
Introduction and aim. This study aims to assess caries experience in children with cleft lip and palate (CLP). Material and methods. A total of 127 children (aged 3-12 years) with CLP and 141 non-cleft controls were assessed for dental caries using the decayed-extracted/missing-filled teeth (deft/DMFT) index. Logistic regression analysis was employed to identify factors associated with dental caries. Statistical tests, including t-test, ANOVA, Chi-square, and Fisher’s exact test, were used to analyze differences between cleft and non-cleft populations. Results. In primary teeth, caries prevalence was significantly higher in children with CLP (63.8%) compared to non-cleft controls (40.4%, p<0.001). The deft scores were 3.30 for CLP and 1.63 for non-CLP group (p<0.01). No significant difference was observed in mean DMFT scores (p=0.02). Significant variations in caries prevalence (p=0.01) and mean DMFT values (p=0.001) were noted in permanent dentition among different cleft groups. Conclusion. Children with CLP show higher caries prevalence and experience, emphasizing the need for targeted dental care interventions in this population. Logistic regression analysis highlights an age-related increase in caries experience among individuals with CLP.
The present study was prospectively conducted in a pediatric population between October 2022 and January 2023 after obtaining approval from the Ethics Committee of Dr R Ahmed Dental College and Hospital, Kolkata (IEC/DCH/089 dated 12/7/2021).
Keywords: cleft lip; cleft palate; dental caries